A expansão universitária e as ações afirmativas: a experiência das cotas afro na Universidade Federal de Santa Maria - Martins, Alcir Luciany Lopes (2014)
Affirmative action as a result of a complex process of struggle for recognition of differences culminate in redistribution policy initiatives as a strategy to reduce or eliminate racial inequali ties in Brazil. Strongly marked by fundamental debates of modernity, the struggles and demands of the Brazilian black movement focus in public debate and in policy and government programs in a decisive way in recent decades. Particularly in the most recent period, note that increasing the presence of the Afro Brazilian population in higher education however this data, statistically observable, requires a closer way to verify that this look has been included and this presence, sharpening the look and making them realize the mobility of black students and how they face the different tests that are submitted while transiting the university space. We seek this approach of individual experience against processes and social networks that constitute the university and, to this end, we follow the Affirmative Action Program UFSM shareholders and the experience of black students in this federal institution of higher education also traversed by macropolitics university expansion.